Features of the use of rehabilitation and recovery measures in the training process of qualified gymnasts - Trofimov, O. B.; Volkov, V. G.; Salaev, A. V.; Gatin, A. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate the effect and effectiveness of the use of the non-steroidal anti-inflammatory drug Amelotex, the chondroprotector Chondrogard, the synovial fluid replacement drug Rusvisk in the complex rehabilitation treatment of qualified gymnasts with post-traumatic prearthrosis of the knee joints.